Management of cysto-biliary communication in hydatid cyst of liver - Bhattarai, A (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Biliary communication of hepatic hydatosis is one of the important complications. It may be minor or major communication. Minor communication is usually diagnosed during operation by the presence of bile stained hydatid fluid on aspiration or bile leak during surgery. However, in major communication, patients present with obstructive jaundice, abdominal pain and cholangitis. Surgical management of major communication is difficult and is associated with high morbidity and mortality. Methods: This is a retrospective study at Tribhuvan University Teaching Hospital, Kathmandu, Nepal over a period of two year (April 15th 2012 to April 15th 2014) and analyzed the medical records of 30 patients admitted and treated for hydatid cyst of liver in surgical ward during that period. Demography, clinical features, management and outcome were analyzed. Results: Of 30 patients with hepatic hydatid cyst operated over a period of two years, thirteen patients had cystobiliary communication. Amongst them, five minor communications were diagnosed during operation and managed with suture plication and omentopexy. Out of the eight major communications, seven were diagnosed preoperatively and all had cholangitis, and one had hydatid cyst of gallbladder and was diagnosed intraoperatively. Among six cases of major communication, five cases required CBD exploration and bile duct reconstruction while partial cholecystectomy was done for hydatid cyst of gall bladder and one case was managed by ERCP sphincterotomy, evacuation of cyst content and stenting. one case was managed with pigtail drain as the patient had infected hydatid cyst and not fit for surgery. Conclusion: Cystobiliary communication is a common complication of hydatid cyst of liver. Therapeutic options are related to size and location of the cyst and size of communication. Journal of Society of Surgeons of Nepal Vol.17(1) 2014: 31-34